2006
DOI: 10.1029/2005gl025127
|View full text |Cite
|
Sign up to set email alerts
|

Using the current seasonal cycle to constrain snow albedo feedback in future climate change

Abstract: [1] Differences in simulations of climate feedbacks are sources of significant divergence in climate models' temperature response to anthropogenic forcing. Snow albedo feedback is particularly critical for climate change prediction in heavily-populated northern hemisphere land masses. Here we show its strength in current models exhibits a factor-of-three spread. These large intermodel variations in feedback strength in climate change are nearly perfectly correlated with comparably large intermodel variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
421
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(451 citation statements)
references
References 16 publications
14
421
2
2
Order By: Relevance
“…Rather, a direct physical linkage, where both present-day behavior and future changes can be shown to be functions of the same process, is desirable. However, as demonstrated in recent work, even in instances where such a linkage would be expected based on simple mechanisms (e.g., [13]), the connection between the present-day and future behavior can be complex.…”
Section: Multi-model Constraintsmentioning
confidence: 91%
See 1 more Smart Citation
“…Rather, a direct physical linkage, where both present-day behavior and future changes can be shown to be functions of the same process, is desirable. However, as demonstrated in recent work, even in instances where such a linkage would be expected based on simple mechanisms (e.g., [13]), the connection between the present-day and future behavior can be complex.…”
Section: Multi-model Constraintsmentioning
confidence: 91%
“…Addressing these contributions and providing an early example of an EC, Hall and Qu [13] assessed the simulated loss of springtime snow cover in the northern hemisphere normalized by warming and demonstrated its strong relationship to the sensitivity of snow cover loss under future warming. Under the assumption that both the present-day and future snow cover losses are driven primarily by temperature, rather than changes in snowfall, the study would seem to provide a simple framework for quantifying a key cryospheric contribution to ECS.…”
Section: Cryospheric and Water Vapor Ecsmentioning
confidence: 99%
“…Groisman et al, 1994;Déry and Brown, 2007). (ii) Hall and Qu (2006) and Fletcher et al (2012) have shown this feedback to be correctly represented only in a minority of the CMIP3 (Coupled Model Intercomparison Project -Phase 3: http://www-pcmdi.llnl.gov/ ipcc/about ipcc.php) models. Due to its low heat conductivity, snow also effectively insulates the underlying soil, with important effects on deep soil temperatures and permafrost extent (Zhang, 2005;Lawrence and Slater, 2010;Gouttevin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For the summer mean precipitation, the RMSE decreases from 3.42 to 3.48 for the Kain-Fritsch and Grell schemes, in southeastern China, but tends to overestimate the summer and annual mean precipitation in the Yangtze River basin, and Southern and Northeastern China regions, which are underestimated by the Grell scheme. The WRF downscaling skill reduction in winter for precipitation may be associated with model deficiencies in representing the snow feedback processes (Hall and Qu, 2006). For the annual cycle of regional mean precipitation, the Grell scheme produces lower correlations with observations than the Kain-Fritsch scheme in most regions, but reduces the wet bias in the Northwest, Northern China and Tibetan Plateau regions.…”
Section: Optimal Ensemble Resultsmentioning
confidence: 99%